Birds as Dads, Babysitters, and Hats: An “Indistinction” Approach to the Mother Bird Mitzvah in Deuteronomy 22:6–7 - Berkowitz, Beth ca. 20./21. Jh. (Worldviews, 2022)
The commandment to send the mother bird from her nest before taking her eggs or chicks, known in Jewish tradition as shiluach hakan, is found in Deuteronomy 22:6–7. This essay addresses dominant perspectives on the mother bird mitzvah—its association with good luck, bad luck, and compassion—before showcasing rabbinic texts from Mishnah and Babylonian Talmud Hullin Chapter 12 that evince interest in birds as ingenious builders, as fathers and not just mothers, as queer parents and altruists, as rebel spirits who resist captivity even unto death and, finally, in birds as co-inhabitants of the earth whose lives are parallel to as well as enmeshed with our own. I offer here a bird-centric approach to the commandment, an effort to read it in a spirit of anti-anthropocentrism, drawing on animal studies scholar Matthew Calarco’s notion of indistinction.